Monitoring Kriteria Kesiapan Penyulang 20 kV Dengan Tampilan Diagram Radar Melalui Aplikasi Google Data Studio PT PLN (Persero) UP2D S2JB - Nita Rosa Damayanti; Nazlena Mohamad Ali (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2025)
In the world of electricity, one important aspect that needs to be considered is the readiness of the 20 kV feeder. The 20 kV feeder is a vital part of the electricity distribution system that is responsible for distributing electrical energy from the substation to customers. Periodic monitoring of the condition of the feeder is very important to ensure the reliability of the electricity supply and prevent disruptions or blackouts. Along with technological developments, monitoring the readiness of the 20 kV feeder can be done more efficiently and effectively using a computerized system. One solution that can be used is to utilize the Google Data Studio application which allows data visualization in the form of a radar diagram. By using the Google Data Studio application, data related to the readiness of 20 kV feeders can be integrated and visualized in the form of an informative radar diagram. This allows technicians and operators to easily identify feeders that require special attention, and take the necessary preventive or corrective actions. The creation of 20 kV feeder readiness monitoring with a radar diagram display through the Google Data Studio application is expected to increase efficiency and effectiveness in monitoring feeder performance, as well as provide a comprehensive picture of the condition of the electricity distribution network. Thus, the reliability of electricity supply can be maintained, and customer satisfaction can be increased.